Historical growth of Eastern Baltic cod (Gadus morhua): Setting a baseline with international tagging data - Mion, Monica; Hilvarsson, Annelie; Hüssy, Karin; Krumme, Uwe; Krüger-Johnsen, Maria; McQueen, Kate; Mohamed, Esha; Motyka, Roman; Orio, Alessandro; Plikshs, Maris; Radtke, Krzysztof; Casini, Michele (Fisheries Research, 2020)
Understanding the growth of commercially exploited fish is crucial in fisheries biology and correct estimations of growth and its change over time are paramount for the evaluation of stock status development. Mark-recapture experiments represent a reliable method to estimate growth when age determination based on otolith reading is uncertain, as is the case of the Eastern Baltic cod stock. In this study, historical data (1955–1970) from tagging experiments on Eastern Baltic cod performed by Sweden, Poland, Denmark, Latvia and Germany were digitised and collated for the first time in a unique dataset to estimate historical von Bertalanffy growth function (VBGF) parameters based on fish length increments using GROTAG model. The estimated VBGF parameters were L∞ =98.22 cm and k=0.14 for the period 1955–1964 (n=1151), L∞ =123.61 cm and k=0.09 for 1965–1970 (n=2612), and L∞=125.60 cm and k=0.09 for the aggregated period (n=3763). A seasonal growth signal was detected for all the periods, with a peak after the spawning season in early autumn. These estimates are the most thorough historical growth baseline now available for the Eastern Baltic cod and can be compared to ongoing and future tagging experiments contributing to the development of stock assessment models for this stock.